2013
DOI: 10.4103/2229-5070.113901
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis: Consensus of treatment and controversies

Abstract: Blastocystis is a highly controversial protozoan parasite. It has been variably regarded as a commensal and pathogen. Scientists have for decades wondered whether it is truly an enteropathogen and if it is observed in symptomatic patients whether treatment is required because patient recovery and improvement has been noted even without any treatment. Though associated with self-limiting infection, treatment is warranted in many patients due to persistence of symptoms. This particularly holds true for children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 31 publications
(67 reference statements)
0
33
0
1
Order By: Relevance
“…A recent review on antimicrobial treatments for Blastocystis suggested that TMP-SMX is a good alternative to metronidazole with fewer side effects and is more cost-effective (34). The review states that it is not known if TMP-SMX has a direct effect on Blastocystis or on the gut bacteria which are essential for Blastocystis survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review on antimicrobial treatments for Blastocystis suggested that TMP-SMX is a good alternative to metronidazole with fewer side effects and is more cost-effective (34). The review states that it is not known if TMP-SMX has a direct effect on Blastocystis or on the gut bacteria which are essential for Blastocystis survival.…”
Section: Discussionmentioning
confidence: 99%
“…The prescription of a triple drug therapy is becoming common practice by some physicians (using secnidazole, furazolidone, and nitazoxanide) (34). The premise behind a triple therapy is that the combination of three drugs will have the highest possible efficacy against the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Blastocystis isolates were not sensitive to other tested herbs such as ginger, black pepper, and white cumin [77]. It has been established that probiotics such as Saccharomices boulardii are equally effective as a symptomatic treatment as metronidazole [13,78].…”
Section: Clinical Significance and Treatmentmentioning
confidence: 99%
“…Other treatment options for blastocystosis include antimicrobials such as, nitazoxanide, furazolidone and emetine, ketoconazole, tinidazole and even the probiotic Saccharomyces boulardii (Sekar and Shanthi, 2013;Stensvold et al, 2010;. To date there is little experimental data to verify the efficacy of the other drugs used for blastocystosis treatment either.…”
Section: Treatmentmentioning
confidence: 99%
“…Metronidazole is the mainstay of treatment for human intestinal protozoa and the first-line therapy for blastocystosis where therapy is required (Coyle et al, 2012;Sekar and Shanthi, 2013;Stensvold et al, 2010;Tan, 2004;.…”
Section: Treatmentmentioning
confidence: 99%